Selectivity in subunit composition of Ena/VASP tetramers. Issue 5 (10th September 2015) - Riquelme, Daisy N.; Meyer, Aaron S.; Barzik, Melanie; Keating, Amy; Gertler, Frank B.
Abstract : Ena/VASP tetramer composition was analysed and mixed oligomerization of Mena with EVL was found to be unfavourable, while other paralogue combinations formed without apparent bias. The tetramerization domain of Ena/VASP proteins is responsible for their selective tetramer formation. Abstract : The members of the actin regulatory family of Ena/VASP proteins form stable tetramers. The vertebrate members of the Ena/VASP family, VASP, Mena and EVL, have many overlapping properties and expression patterns, but functional and regulatory differences between paralogues have been observed. The formation of mixed oligomers may serve a regulatory role to refine Ena/VASP activity. While it has been assumed that family members can form mixed oligomers, this possibility has not been investigated systematically. Using cells expressing controlled combinations of VASP, Mena and EVL, we evaluated the composition of Ena/VASP oligomers and found that VASP forms oligomers without apparent bias with itself, Mena or EVL. However, Mena and EVL showed only weak hetero-oligomerization, suggesting specificity in the association of Ena/VASP family members. Co-expression of VASP increased the ability of Mena and EVL to form mixed oligomers. Additionally, we found that the tetramerization domain (TD) at the C-termini of Ena/VASP proteins conferred the observed selectivity. Finally, we demonstrate that replacement of the TD with a synthetic tetramerizing coiled coil sequence supports homo-oligomerization and normal VASP subcellular localization.